The Possibility of issuing a Palestinian Currency using Hypothetical options which may suited the Specificity of the Palestinian Economy ) Between support and opposition( - عزمي وصفي عوض (Revue du contrôle, de la comptabilité et de l’audit, 2020)
This study sought to identify the possibility of issuing a Palestinian currency using hypothetical options which may suited the Specificity of the Palestinian Economy, This is an optimistic vision of the nature of the Palestinian monetary arrangements in light of the freeze of peace agreements, absence of Palestinian currency and seize of the Palestinian Financial dues by the Zionist Entity. These hypothetical options were Crystallized as the Palestinian currency is critical to the Palestinian economy and it is also significant in reducing the economic losses including seigniorage. To this end, the researcher conducted a statistical test to explore the perspective of the academic experts in this field. The study findings showed no statistically significant differences at (α ≤ 0. 05) on respondents’ attitudes towards the possibility of using hypothetical options to issue a currency attributed to demographic variables. The researcher recommended that the institution in charge of managing and issuing a Palestinian currency should be the currency board which is entitled to introduce it gradually side by side with other foreign currencies in circulation, The study also recommended partial issuing of the total currency with a limit of currency in circulation) cc( instead of total issuing to cover the entire money supply in the narrow sense (M1). Finally, the researcher recommended using hypothetical options related to exchange rates, currency value and reserve cover.